Analysis of Factors Influencing Interest in Cryptocurrency Investment - Andini; Indriany, Poppy (Research Horizon, 2025)
The rapid digital transformation and growing popularity of cryptocurrencies have reshaped investment behavior worldwide, particularly in emerging economies where access to digital assets is expanding alongside financial literacy challenges. This study aimed to systematically examine the influence of knowledge, experience, risk tolerance, and peer influence on individual interest in investing in crypto assets within the cryptocurrency community in Palembang City. This study employed a causal associative approach with a quantitative approach. Data collection was conducted by distributing questionnaires to 225 participants, identified based on research criteria and representing members of the crypto community. Data analysis was conducted using Structural Equation Modeling Partial Least Squares (SEM-PLS) with the assistance of SmartPLS software version 4.1.0.9. The analysis findings indicate that, partially, the variables knowledge, experience, and peer influence significantly influence interest in investing in cryptocurrency. Meanwhile, risk tolerance did not have a significant effect. A simultaneous review of all four variables demonstrated a strong statistical relationship with an individual’s interest in investing. The findings of this study align with the concept of the theory of planned behavior, which theoretically emphasizes that attitudes, subjective norms, and perceptions of self-control play a key role in shaping an individual’s interest in taking a particular action.